2011
DOI: 10.1161/circulationaha.110.991505
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Bridge to Heart Transplantation Among Children in the United States

Abstract: Background-Extracorporeal membrane oxygenation (ECMO) has served for Ͼ2 decades as the standard of care for US children requiring mechanical support as a bridge to heart transplantation. Objective data on the safety and efficacy of ECMO for this indication are limited. We describe the outcomes of ECMO as a bridge to heart transplantation to serve as performance benchmarks for emerging miniaturized assist devices intended to replace ECMO. Methods and Results-Data from the Extracorporeal Life Support Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(63 citation statements)
references
References 25 publications
4
58
1
Order By: Relevance
“…Further analysis of infant EXCOR outcomes is warranted. Although survival for EXCOR patients is clearly superior to survival after ECMO for children >5 kg, a survival advantage is more difficult to demonstrate in children <5 kg on the basis of the published ECMO experience, 3,18,19 although individual center experiences may vary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis of infant EXCOR outcomes is warranted. Although survival for EXCOR patients is clearly superior to survival after ECMO for children >5 kg, a survival advantage is more difficult to demonstrate in children <5 kg on the basis of the published ECMO experience, 3,18,19 although individual center experiences may vary.…”
Section: Discussionmentioning
confidence: 99%
“…The EXCOR is a pneumatically driven paracorporeal blood pump manufactured in 5 sizes (10,25,30,50, and 60 cm 3 ) and is capable of providing both left VAD and biventricular VAD (BIVAD) support. 5 The trial design, inclusion criteria, and end points have been reported previously.…”
Section: Study Population and Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…22 An international database showed that extracorporeal membrane oxygenation does not appear to be a reliable long-term circulatory support for children awaiting heart transplantation. 23 Fortunately, other options of support exist, and Stiller et al 24 provide a useful overview of mechanical cardiovascular support in infants and children.…”
Section: Cardiomyopathy Heart Failure and Transplantationmentioning
confidence: 99%
“…An international database showed that extracorporeal membrane oxygenation does not appear to be a reliable long-term circulatory support for children awaiting heart transplantation (23). Fortunately, other options of support exist, and Stiller et al (24) provide a useful overview of mechanical cardiovascular support in infants and children.…”
Section: Fetal Cardiologymentioning
confidence: 99%